THE EFFECT OF AMYLUM ADHESIVE AND SAWDUST COMPOSITION FOR RUBBER SEED SHELL BIO-BRIQUETTE AS AN ENVIRONMENTALLY FRIENDLY ALTERNATIVE FUEL - Fathia Eka Pratiwi; Pitri Yenica; Maulidia Putri (OISAA, 2018)
The purpose of this reaserch is to determine the optimum composition of rubber seed shell, sawdust,and amylum adhesive. Experiments were carried out in several stages: aggregate of the raw materials,drain the raw materials, do carbonization or combustion with 600°C temperature for 2 hours, restrict thesupply of oxygen so that the materials do not burn to ashes, sieve the materials, weigh each ofingredients in the ratio of 60:20:20, 50:20:30, 40:20:40, and 30:20:50, blend the materials, print thebriquettes, drain, and analyze the contents of briquette. This reasearch generates optimumcompositionwith ratioof 60% rubber seed shells, 20% sawdust and 2 % amylum adhesive. It is in termsof the parameters that have been analyzed in the form of spesification of inherent moisture is 4.99%,ash content is 4.38%, volatile matter content is 24.75%, fixed carbon is 66.38% and calorific value is6069 cal/gr.